Constraints and Strategies for Enhancing Pig Production in Delta State, Nigeria (Global Journal of Science Frontier Research, 2015)
This study examined constraints and strategies for enhancing pig production. The study was carried out in Delta State, Nigeria. A sample size of 90 respondents was used for the study. Data were collected using a structured and validated interview schedule. Data for the study were analyzed using descriptive and inferential statistics. Frequency count, percentage and mean scores were used to summarize data, while factor analysis was used to ascertain constraints to pig production. Results of the study reveal that economic, poor management and socio-cultural biases were the major factors hindering pig production in Delta State. Specific issues highlighting these factors were also identified. Strategies for enhancing pig production that were identified by the study include: establishment of functional market for pig and pig products, subsidy for pig housing and equipment, adoption of improved pig production technologies, provision of transport facilities, subsidy for pig feeds, special credit scheme for pig farmers, public enlightenment on the nutritional value of pigs, enacting legislation against discrimination of pig products, and making veterinary services available and affordable.
Keywords: pigs; constraints; strategies; production delta state; nigeria